2016
DOI: 10.3389/fmicb.2016.01538
|View full text |Cite
|
Sign up to set email alerts
|

Endophytes: A Treasure House of Bioactive Compounds of Medicinal Importance

Abstract: Endophytes are an endosymbiotic group of microorganisms that colonize in plants and microbes that can be readily isolated from any microbial or plant growth medium. They act as reservoirs of novel bioactive secondary metabolites, such as alkaloids, phenolic acids, quinones, steroids, saponins, tannins, and terpenoids that serve as a potential candidate for antimicrobial, anti-insect, anticancer and many more properties. While plant sources are being extensively explored for new chemical entities for therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
311
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(388 citation statements)
references
References 60 publications
2
311
0
9
Order By: Relevance
“…More than 200 bacterial genera have been identified to be entophytes. Endophytes have attracted scientists' attention in the biotechnological sector recently . It is reported that the endogenous natural products produced by endophytes have unique structures and high biological activity, and these bacteria are a huge source of useful materials in medicine, agriculture, and the industry .…”
Section: Introductionmentioning
confidence: 99%
“…More than 200 bacterial genera have been identified to be entophytes. Endophytes have attracted scientists' attention in the biotechnological sector recently . It is reported that the endogenous natural products produced by endophytes have unique structures and high biological activity, and these bacteria are a huge source of useful materials in medicine, agriculture, and the industry .…”
Section: Introductionmentioning
confidence: 99%
“…These microorganisms are part of complex systems of balanced interactions mediated by natural products between endophytes and their host 46 . The biotechnological interest in endophytic microbes due to their potential as sources of natural products began with the discovery of paclitaxel 7 , and subsequent reports of other important bioactive molecules from endophytes, such as deoxypodophyllotoxin 8 , maytansine 9, 10 , campthotecin 11, 12 , among many others 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of this plant in folk medicine 42, 43 , and the interesting biosynthetic potential of endophytic microorganisms 13 , we initiated the investigation of natural products from endophytes of L . ericoides 44 .…”
Section: Introductionmentioning
confidence: 99%
“…Host specificity is the relationship in which a fungus is restricted to a single host or a group of related species, but does not occur in other unrelated plants in the same habitat. [7][8][9][10][11] A single endophytic fungal species may form relationships with two related plant species, but demonstrate a preference for one particular host and this phenomenon is called as host selectivity. The host specificity is also used to indicate the differences in fungal community, compositions and isolation frequencies from different host plants.…”
Section: Introductionmentioning
confidence: 99%